Korupcja władz samorządowych jako zagrożenie dla gospodarki lokalnej - Laskowski, Piotr (Corruption of the Council Authorities as a Menace to the Local Economy, 2006)
The change of the socio-economic system in Poland as well as the transformation of the national economy have brought about the interest in corruption. The main reason for this disastrous pathology, which is being currently experienced in Poland, is the weak, malfunctioning and bureaucratic structure of the local and central authorities. The high rate of corruption means malfunctioning of many institutions. As a result, the country's chances of meaningful development become weaker. In the common judgment, corruption has already penetrated all spheres of the institutional life in our country. The local council in Poland is not free from this problem either. Local councils, as the units representing mere mortals, should be theoretically better controlled by citizens since working in a given area, they have direct contact with local communities and therefore they are open to the temptation of corruption. As a matter of fact, there are two main factors that influence the growing phenomenon of corruption. Firstly, there is a strong link between political parties and local councilors. Secondly, there are a lot of procedures that effectively deprive voters of the control over their councilors. It turns out that the civic society in our country is still not developed enough. Thus citizens do not feel co-responsibility for the functioning of local councils. Furthermore, people do not feel the need to check local authorities. The results of the public opinion poll have indicated that the phenomenon of corruption is deeply-rooted in our social consciousness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 388-397